Coherent radiation of relativistic electrons in dielectric fibers in the millimeter wavelength range; JETP Letters; Vol. 100, iss. 12 - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Bleko V. V. Vitold Vladislavovich; Soboleva V. V. Veronika Vyacheslavovna (2015, 2015)
Title screen